Pelaksanaan Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kinerja Guru (Studi Kasus di SMP Negeri 28 Maluku Tengah) - Yan Hattu; T.G. Ratumanan; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The aim of this research is to: describe the implementation and results of the principal's academic supervision in improving teacher performance at Public Junior High School 28 Central Maluku. Describe the principal's academic supervision planning in improving teacher performance at Public Junior High School 28 Central Maluku. Describe the implementation of the principal's academic supervision in improving teacher performance at Public Junior High School 28 Central Maluku. Describe the results of supervision and follow-up to the implementation of the principal's academic supervision in improving teacher performance at Public Junior High School 28 Central Maluku. Describe the supporting and inhibiting factors for planning and implementing academic supervision of the principal of Public Junior High School 28 Central Maluku. The type of research used in this research is a case study, which does not just explain what the object being studied is like, but how it exists and why the case occurred. This research was conducted for three months on teachers, school principals, 2 senior teachers who have served more than 15 years and are certified, 3 teachers, 1 each representing class VII, VIII and class IX and 1 Public Junior High School 28 Central Maluku. Data collection techniques used were interviews, direct observation, participant observation, documentation and archival recordings. Based on data from research findings and the results of the analysis of the implementation of the principal's academic supervision in improving the performance of teachers at Public Junior High School 28 Central Maluku, in the planning of academic supervision the principal has planned the implementation of academic supervision in a programmed manner in accordance with the results of the school work meeting at the beginning of the school year, the implementation of academic supervision in accordance with with the school academic calendar, the principal uses supervision instruments to assess teachers in class, the principal uses individual supervision techniques through class visits, final results and follow-up of academic supervision, the principal carries out follow-up individually and generally in meetings with the teacher council, and the supervision evaluation process is carried out individually as well as supporting factors for academic supervision and inhibiting factors for academic supervision, namely the number of teachers and groups that provide the level of effectiveness in implementing the principal's academic supervision, the similarity of the academic supervision schedule with the school principal's official activities, differences in competence in certain fields of science between school principals. and subject teachers and limited learning facilities and media for certain subject teachers.